An Energy Efficient Approach for Routing in Wireless Sensor Networks. (2016) - Warrier, Maya M.; Kumar, Ajay
Abstract: Wireless Networks are becoming popular due to the concept of "3 any"-any person, anywhere and anytime. Technological advancements in wireless communication paved way to the development of tiny low-cost, low-power and multifunctional sensor nodes in wireless sensor networks. The network layer deals with routing issues in sensor networks. Since radio transmission and reception consumes large amount of energy, power is an important factor to be investigated on. Energy conservation is thus a key issue in wireless sensor networks. Ongoing research involves designing routing protocols that requires less energy during communication thereby extending the networks lifetime. For most of the applications, a replacement of energy is too expensive. An energy harvesting wireless sensor networks make use of nodes that are able to harvest energy from environment. This paper provides a survey on energy efficient routing. A comparison between Modified LEACH and Mobile Sink improved energy-efficient PEGASIS-based routing protocol is done using MATLAB. Paper also introduces the energy harvesting concept.